Fission-fusion dynamics: new research frameworks - Aureli, F; Schaffner, C; Boesch, C; Bearder, S; Call, J; Chapman, C; Connor, R; Di Fiore, A; Dunbar, R; Henzi, S; Holekamp, K; Korstjens, A; et al. (University of Chicago Press, 2008)
Renewed interest in fission-fusion dynamics is due to the recognition that such dynamics may create unique challenges for social interaction and distinctive selective pressures acting on underlying communicative and cognitive abilities. New frameworks for integrating current knowledge on fission-fusion dynamics emerge from a fundamental rethinking of the term "fission-fusion" away from its current general use as a label for a particular model type of social system (i.e., "fission-fusion societies"). Specifically, because the degree of spatial and temporal cohesion of group members varies both within and across taxa, any social system can be described in terms of the extent to which it expresses fission-fusion dynamics. This perspective has implications for socioecology, communication, cognitive demands, and human social evolution.